Problem Konsep Monoteisme dalam Agama-Agama Semit - Hasbi Arijal (Universitas Darussalam Gontor, 2015)
Is there similarities between Judaism, Christianity, and Islam? If there, where is the similarity? And if so, why they are not be united, would not it be more powerful and far reaching if they are united? Then how about the position and posture or attitude of these religions on the issue of monotheism, while the pluralists use it as a means to spread understanding of religious pluralism? The pluralists are also using the issue to gain legalization that Judaism, Christianity and Islam is actually same in the concept of God, the same God worshiped single or monotheist. It’s mean, the three religions in essence no significant differences. So that it can together accept the truth of the concept of God of each religion without blame. This simple paper will examine that issue with a few critical questions. The critical questions aiming to find an obvious point, it is true the assumption that the three Semitic religions are monotheistic and can be united under the shelter of monotheism. At the end of this article will be explained how the position of three religions toward monotheistic.